Analysis of second-generation epigenetic clocks reveals further associations between disproportionate biological ageing and hippocampal volume - Lidija Milicic; Michael Vacher; Vincent Doré; Pierrick Bourgeat; Rosita Shishegar; James D. Doecke; Paul Maruff; Christopher C. Rowe; Victor L. Villemagne; Michael Weiner; Paul Aisen; Ronald Petersen; et al. (GeroScience, 2026)

Faunal community ecology of central-eastern Indian Ocean Seamounts - Timothy D. O'Hara; Shane T. Ahyong; Phil Alderslade; Dianne Bray; Francesco Criscione; Niki Davey; Caroline Farrelly; Martin F. Gomon; Ana Hara; Jeremy Horowitz; Andrew M. Hosie; Lisa Kirkendale; et al. (Deep Sea Research Part II: Topical Studies in Oceanography, 2026)

Comparison of Laboratory Confirmed Drugs in Acute Recreational Drug Toxicity Presentations to an Urban Hospital in London, UK, 2016/17 versus 2019/20 - Caitlin E Wolfe; Lachlan J Sund; John RH Archer; Ashley Rowe; Simon Hudson; David M Wood; Paul I Dargan (Journal of Medical Toxicology, 2025)
Introduction Novel Psychoactive Substance (NPS) use is increasingly prevalent and is often associated with severe acute recreational drug toxicity (ARDT). 258 UK deaths were attributed to NPS use in 2021. Confirmatory testing which identifies NPS is limited by expense and timeliness. We aimed to identify NPS and other recreational drugs in a sample of 1000 ARDT presentations to a central London hospital in 2019/20 and to compare these drugs to those identified from a previous cohort in 2016/2017. Methods We prospectively enrolled 1000 serum samples from ARDT presentations to St Thomas’ Hospital between February 2019 and February 2020. Serum samples were deidentified and underwent qualitative analysis via mass spectrometry. Results were returned at the conclusion of testing and statistical analysis performed using ‘R’ (R Foundation for Statistical Computing). Results Twenty-eight unique NPS were detected in 2019/20, compared to 31 in 2016/17. Eight new NPS were detected in 2019/20: four benzodiazepines, two synthetic cannabinoid receptor agonists, one cathinone and one ketamine-analogue. No NPS opioids were detected in either cohort. Cannabis (16%,11% p = 0.02), ketamine (12%,7% p < 0.01) and opioids (57%,24% p < 0.01) were detected significantly more frequently in 2019/20 than in 2016/17, while alcohol (22%,49% p < 0.01), cathinones (1%,15% p < 0.01), GHB (14%,20% p < 0.01) and MDMA (9%,18% p < 0.01) were detected less frequently. Conclusions Studies that utilise confirmatory testing to detect NPS in presentations of ARDT provide important information for public health interventions. More NPS benzodiazepines and fewer NPS cathinones were detected in 2019/20, following temporal trends of forensic detection throughout Europe and reinforcing the importance of identifying emerging drugs.

Comprehensive analysis of epigenetic clocks reveals associations between disproportionate biological ageing and hippocampal volume - Lidija Milicic; Michael Vacher; Tenielle Porter; Vincent Doré; Samantha C. Burnham; Pierrick Bourgeat; Rosita Shishegar; James Doecke; Nicola J. Armstrong; Rick Tankard; Paul Maruff; Colin L. Masters; et al. (GeroScience, 2022)
The concept of age acceleration, the difference between biological age and chronological age, is of growing interest, particularly with respect to age-related disorders, such as Alzheimer’s Disease (AD). Whilst studies have reported associations with AD risk and related phenotypes, there remains a lack of consensus on these associations. Here we aimed to comprehensively investigate the relationship between five recognised measures of age acceleration, based on DNA methylation patterns (DNAm age), and cross-sectional and longitudinal cognition and AD-related neuroimaging phenotypes (volumetric MRI and Amyloid-β PET) in the Australian Imaging, Biomarkers and Lifestyle (AIBL) and the Alzheimer’s Disease Neuroimaging Initiative (ADNI). Significant associations were observed between age acceleration using the Hannum epigenetic clock and cross-sectional hippocampal volume in AIBL and replicated in ADNI. In AIBL, several other findings were observed cross-sectionally, including a significant association between hippocampal volume and the Hannum and Phenoage epigenetic clocks. Further, significant associations were also observed between hippocampal volume and the Zhang and Phenoage epigenetic clocks within Amyloid-β positive individuals. However, these were not validated within the ADNI cohort. No associations between age acceleration and other Alzheimer’s disease-related phenotypes, including measures of cognition or brain Amyloid-β burden, were observed, and there was no association with longitudinal change in any phenotype. This study presents a link between age acceleration, as determined using DNA methylation, and hippocampal volume that was statistically significant across two highly characterised cohorts. The results presented in this study contribute to a growing literature that supports the role of epigenetic modifications in ageing and AD-related phenotypes.

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Lake morphometry determines Dreissena invasion dynamics - Alexander Y. Karatayev; Vadim A. Karatayev; Lyubov E. Burlakova; Knut Mehler; Mark D. Rowe; Ashley K. Elgin; Thomas F. Nalepa (Biological Invasions, 2021)

mGluR5 Allosteric Modulation Promotes Neurorecovery in a 6-OHDA-Toxicant Model of Parkinson’s Disease - Kyle Farmer; Khaled S. Abd-Elrahman; Alexa Derksen; Elyn M. Rowe; Ashley M. Thompson; Christopher A. Rudyk; Natalie A. Prowse; Zachary Dwyer; Samantha C. Bureau; Teresa Fortin; Stephen S.G. Ferguson; Shawn Hayley (Molecular Neurobiology, 2020)

Influence of invasive quagga mussels, phosphorus loads, and climate on spatial and temporal patterns of productivity in Lake Michigan: A biophysical modeling study - Mark D. Rowe; Eric J. Anderson; Henry A. Vanderploeg; Steven A. Pothoven; Ashley K. Elgin; Jia Wang; Foad Yousef (Limnology and Oceanography, 2017)
We applied a three‐dimensional biophysical model to Lake Michigan for the years 2000, 2005, and 2010 to consider the mechanisms controlling spatial and temporal patterns of phytoplankton abundance (chlorophyll a ) and lake‐wide productivity. Model skill was assessed by comparison to satellite‐derived Chl a and field‐measured water quality variables. We evaluated model sensitivity to scenarios of varying mussel filter feeding intensity, tributary phosphorus loads, and warm vs. cool winter‐spring climate scenarios. During the winter‐spring phytoplankton bloom, spatial patterns of Chl a were controlled by variables that influenced surface mixed layer depth: deep mixing reduced net phytoplankton growth through light limitation and by exposing the full water column to mussel filter feeding. Onset of summer and winter stratification promoted higher surface Chl a initially by increasing mean light exposure and by separating the euphotic zone from mussels. During the summer stratified period, areas of relatively high Chl a were associated with coastal plumes influenced by tributary‐derived nutrients and coastal upwelling‐downwelling. While mussels influenced spatial and temporal distribution of Chl a , lake‐wide, annual mean primary production was more sensitive to phosphorus and warm/cool meteorology scenarios than to mussel filter feeding scenarios. Although Chl a and primary production declined over the quagga mussel invasion, our results suggest that increased nutrient loads would increase lake‐wide productivity even in the presence of mussels; however, altered spatial and temporal patterns of productivity caused by mussel filter feeding would likely persist.